The Effect of Exercises with a Proposed Device to Improving Some Bio-Kinematic Variables and the Performance of the Arab Round off Skill on Floor Movement Mat Device of the Artistic Gymnastics for Women - Zahraa Salah Abd Ali; Bushra Kazem Abdel Reda (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in preparing exercises using a proposed device to learn the skill of thehuman wheel on a machine rug of ground movements of the artistic gymnastics. As for the research problem:Through the presence of the two researchers as teachers and observers of this sport in the gymnastics hall,they noticed that there is difficulty in the students’ performance of the skill of the round off on the machineof the mat of ground movements, according to the researchers’ opinion, the reason for this is that skillsare taught with the limited availability of assistive devices, as well as the lack of use of these devices inexercises according to biomechanical variables, although they facilitate the learning process for these skillsand work to shorten the time and effort in the learning process and enable the removal of the difficultiesencountered before. As for the objectives of the research : Design and manufacture of a device that teachesthe skill of the round off and helps in overcoming the difficulty of performing that skill for female studentsand preparing exercises with a proposed device to learn the skill of the human wheel on the machine of theground movements mat in the artistic gymnastics of the students.